The Khandaq Shapur: Defense, Irrigation, Boundary, Frontier - Michelle de Gruchy; Jaafar Jotheri; Hayder Alqaragholi; Jassim Al-Janabi; Raheem Alabdan; Haneen Al-Talaqani; Ghadeer Almamouri; Hajir Al-Rubaye (Land, 2021)
Khandaq Shapur has been named one of the great barriers of the ancient world, but very little is known about the monumental-scale linear feature. This interdisciplinary paper brings together archaeologists and historians to present (1) an updated history of the Khandaq Shapur drawing upon a wider range of sources, including Arabic scholarly sources, and (2) a modern map of the Khandaq Shapur produced from a ground truthed remote sensing using historic Corona satellite imagery from the 1960s and imagery available in Google Earth. This new map of the Khandaq Shapur’s ground truthed location is compared to the known locations of Sasanian sites from previous archaeological surveys to contextualise the Khandaq Shapur within the wider archaeological landscape. Together, the landscape archaeology and historical evidence provide a comprehensive picture of this unique feature: shedding light not only on its precise location, but also its nature (what was it?) and how it was used over time.